Optoelectrical properties of Al/p-Si/Fe:N doped ZnO/Al diodes - Coskun, B.; Mensah-Darkwa, K.; Soylu, M.; Al-Sehemi, Abdullah G.; Dere, A.; Al-Ghamdi, Ahmed; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2018)
In this work, 3% Fe doped zinc oxide (ZnO) doped by Nitrogen thin films were grown by reactive radio frequency magnetron sputtering on p-Si substrates. The structural and optical properties of the 3% Fe doped ZnO doped by Nitrogen thin films were investigated by the scanning electron microscope and spectrophotometry. The diodes with the configuration of Al/p-Si/3% Fe-ZnO: N/Al have been fabricated and it has been observed that the diodes exhibit a good rectification. The optical band gap was found to be 3.98 +/- 0.02 eV for 3% Fe doped ZnO: N thin film deposited at the N-2 flow rate of 15 sccm. The electrical parameters of the diode were determined using Cheung's and Norde's method. The capacitance-voltage and conductance-voltage characteristics of Al/p-Si/3% Fe-ZnO: N/Al structure have been investigated in the frequency range 10 kHz-1 MHz. The increase in capacitance at lower frequency is attributed to the density of interface states. It is evaluated that the prepared diodes can be used as nanoscale electronic and optoelectronic devices.
Keywords: Zinc oxide; Sputtering; Optical properties; Diode